Associations Between the Kynurenine Pathway, Proinflammatory Cytokines, and Brain-Derived Neurotrophic Factor in Hospitalized Patients With Chronic Schizophrenia: A Preliminary Study - Naomichi Okamoto; Tomoya Natsuyama; Ryohei Igata; Yuki Konishi; Hirofumi Tesen; Atsuko Ikenouchi; Reiji Yoshimura (Frontiers in Psychiatry, 2021)
Purpose: The kynurenine (Kyn) pathway may play a role in the pathophysiology of schizophrenia. This pathway shows crosstalk with proinflammatory cytokines, including interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α), and/or brain-derived neurotrophic factor (BDNF). Moreover, Kyn metabolites affect neurotransmission and cause neurotoxicity. To date, the influence of the Kyn pathway on proinflammatory cytokines and BDNF remains to be fully elucidated. The aim of this study was to investigate the relationships of the Kyn pathway with proinflammatory cytokines, BDNF, and psychiatric symptoms in patients with schizophrenia.Methods: Thirty patients with schizophrenia and ten healthy control participants were recruited for this study. All patients were diagnosed with schizophrenia using the Diagnostic and Statistical Manual for Mental Disorders, Fifth Edition (DSM-5). The healthy controls were those who did not fulfill any of the diagnostic criteria in the DSM-5. The serum levels of Kyn and its metabolites, proinflammatory cytokines, and BDNF were measured in patients with schizophrenia and healthy controls. Patients with schizophrenia were also assessed for psychiatric symptoms using the Positive and Negative Syndrome Scale (PANSS).Results: Patients with schizophrenia and healthy controls showed no significant differences in the levels of Kyn and its metabolites, proinflammatory cytokines, and BDNF. A significant positive correlation was found between the serum levels of TNF-α and Kyn (r = 0.53, p = 0.0026) and the Kyn/tryptophan (Trp) value (r = 0.67, p = 0.000046) in the schizophrenia group, but not in the healthy control group.Conclusion: TNF-α affects the Kyn pathway in patients with chronic schizophrenia, but not in the healthy individuals, although serum TNF-α levels showed no difference between the two groups. Associations between the Kyn pathway and the levels of proinflammatory cytokines and BDNF or psychotic symptoms might be complicated in hospitalized patients with chronic schizophrenia.